Review of Surgery - Panda UN, Sahoo PK; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2006)
Multiple Choice Questions now form the standard format for assessment of candidates in most competitive examinations. So many universities have introduced this pattern in undergraduate medical examinations. Hence, students need to be oriented about MCQs from the very beginning of their career. Properly formulated MCQs cover all aspects of a topic from aetiology to prognosis and can be useful in viva voce as well as in clinical examinations. This third edition is spread over in 81 chapters while retaining most of the MCQs of the previous edition. New MCQs have also been incorporated but all the five practice papers are left undisturbed. More stress has been put on MCQs that have clinical significance. Every effort has been made to provide the most appropriate answers, still chances of omissions cannot be ruled out due to oversight. Students are advised to consult the page reference given against each MCQ.
Keywords: MCQs and Self-assessment,Surgery; Electronic books